Predictive Role of Acute Phase Reactants in the Response to Therapy in Patients with Chronic Hepatitis C Virus Infection - Oguz, Ayten; Atay, Ahmet Engin; Tas, Adnan; Seven, GÜLSEREN; SEVEN, GÜLSEREN; Koruk, Mehmet (My University, 2013)
Background/Aims: Biochemical parameters and acute-phase proteins (APPs) may provide complementary data in patients with chronic hepatitis C (CHC). We aimed to evaluate the predictive role of APPs in the response to antiviral therapy. Methods: Forty-five patients underwent antiviral therapy. Serum ferritin, C-reactive protein (CRP), transferrin, albumin, alpha-1 acid glycoprotein (A1AG), and alpha-2 macroglobulin (A2MG) levels were examined at the initial evaluation and at the 4th, 12th, and 48th weeks. HCV RNA levels were examined at the initial evaluation and at the 12th and 48th weeks. Results: Ferritin, transferrin, A1AG, and A2MG levels were significantly higher in the patient group (p<0.05). CRP, ferritin, A1AG, and A2MG levels were significantly increased from baseline to the 4th week (p<0.05). The responders and nonresponders to antiviral therapy had insignificantly but remarkably different levels of CRP, ferritin, transferrin, A1AG, A2MG, and alanine aminotransferase (ALT) both at the initial evaluation and at the 12th week. Conclusions: Variations in ferritin, A1AG, A2MG, albumin, CRP, and transferrin levels are not alternatives to virological and biochemical parameters for predicting an early response to therapy in patients with CHC. However, the investigation of ALT levels and hepatitis C virus RNA in combination with acute-phase reactants may provide supplementary data for evaluating responses to antiviral therapy. (Gut Liver 2013;7:82-88)
Keywords: Gastroenterology